Genetic and biochemical identification of a novel single-stranded DNA-binding complex in Haloferax volcanii - Stroud, Amy; Liddell, Susan; Allers, Thorsten (Frontiers, 2012)
Single-stranded DNA (ssDNA)-binding proteins play an essential role in DNA replication and repair. They use oligonucleotide/oligosaccharide-binding (OB)-folds, a five-stranded β-sheet coiled into a closed barrel, to bind to ssDNA thereby protecting and stabilizing the DNA. In eukaryotes the ssDNA-binding protein (SSB) is known as replication protein A (RPA) and consists of three distinct subunits that function as a heterotrimer. The bacterial homolog is termed SSB and functions as a homotetramer. In the archaeon Haloferax volcanii there are three genes encoding homologs of RPA. Two of the rpa genes (rpa1 and rpa3) exist in operons with a novel gene specific to Euryarchaeota; this gene encodes a protein that we have termed RPA-associated protein (rpap). The rpap genes encode proteins belonging to COG3390 group and feature OB-folds, suggesting that they might cooperate with RPA in binding to ssDNA. Our genetic analysis showed that rpa1 and rpa3 deletion mutants have differing phenotypes; only Δrpa3 strains are hypersensitive to DNA damaging agents. Deletion of the rpa3-associated gene rpap3 led to similar levels of DNA damage sensitivity, as did deletion of the rpa3 operon, suggesting that RPA3 and RPAP3 function in the same pathway. Protein pull-downs involving recombinant hexahistidine-tagged RPAs showed that RPA3 co-purifies with RPAP3, and RPA1 co-purifies with RPAP1. This indicates that the RPAs interact only with their respective associated proteins; this was corroborated by the inability to construct rpa1 rpap3 and rpa3 rpap1 double mutants. This is the first report investigating the individual function of the archaeal COG3390 RPA-associated proteins (RPAPs). We have shown genetically and biochemically that the RPAPs interact with their respective RPAs, and have uncovered a novel single-stranded DNA-binding complex that is unique to Euryarchaeota.